Usage Intention of QR Mobile Payment System Among Millennials in Malaysia - Mohd Uzairi, Ahmad Hajazi; Seng, Sou Chan; Siti Aisyah, Ya'kob; Fadilah, Siali; Hamrila, Abdul Latip (Human Resource Management Academic Research Society, 2021)
In line with the growth of smartphone and internet penetration, there is a growing trend of cashless payment made via smartphone, or mobile payment system, especially among millennials in Malaysia. Despite its advantages - which includes convenience, fast, and efficient among others – the adoption of the mobile payment system is still low. In this research, the usage intention of QR mobile payment system is observed through seven dimensions, namely perceived usefulness, perceived ease of use, perceived security, perceived compatibility, social influence, rewards, and personal innovativeness. 300 set of questionnaires was distributed among millennials as target respondents, and the data was analyzed using Pearson Correlation Analysis. The result showed that except social influence, all six other dimensions showed a significant and positive relationship with usage intention of QR mobile payment system.